Atividade da enzima nitrato redutase em cultivares de arroz de terras altas - Moro, Edemar; Crusciol, Carlos Alexandre Costa [UNESP]; Nascente, Adriano Stephan; Cantarella, Heitor (My University, 2014)
The cultivation of upland rice seems to be, among the major crops, the least adapted to the notillage system (NTS). One of the reasons attributed to this lower adaptation to NTS would be the low activity of the nitrate reductase enzyme (NR), which would hinder the nitrogen absorption by seedlings. However, there may be differences in the enzyme activity among the rice genotypes. Therefore, the aim of this study was to evaluate the activity of NR enzyme in distinct upland rice cultivars and in different times of crop early development. The experiment was performed under controlled conditions, with experimental design in a completely randomized block in factorial scheme 10 (rice cultivars) x 4 (assessment times) with four replications. The evaluations of NR activity were carried out in the middle third of fresh leaf tissue. There was interaction between cultivars and evaluation time (p = 0.0178). The enzymatic activity of NR was higher in IAC 202, at 7 days after emergence (DAE). At 14 DAE, the cultivars Carajás, IAC 202, BRS Sertaneja, BRS Curinga and BRS Bonança showed high activity of this enzyme. At 21 DAE, the enzymatic activity was higher in cultivars Primavera and BRS Bonança. However, at 28 DAE, there were no differences among cultivars for this variable. We conclude that NR enzyme activity in upland rice crop is dependent of cultivar, period of plant development and decreases with the advancement of the crop cycle.

O cultivo do arroz no ambiente terras altas parece ser, dentre as principais culturas, o menos adaptado ao sistema plantio direto (SPD). Uma das razões atribuídas para esta menor adaptação ao SPD seria a baixa atividade da enzima nitrato redutase (NR), o que dificultaria a assimilação de nitrogênio pelas plântulas. Entretanto, pode haver diferenças entre os genótipos quanto à atividade dessa enzima. Desse modo, o objetivo deste trabalho foi determinar a atividade da enzima NR em distintos cultivares de arroz de terras altas e em diferentes épocas do início de desenvolvimento da cultura. O experimento foi conduzido em condições controladas, em delineamento experimental em blocos completos casualizados com os tratamentos arranjados em esquema fatorial, 10 (cultivares de arroz) x 4 (épocas de avaliações), com quatro repetições. As avaliações da atividade da enzima NR foram realizadas no terço médio do tecido foliar fresco. Houve interação entre cultivares e épocas de avaliação (p=0,0178). A atividade enzimática da NR foi superior na cultivar IAC 202, aos 7 dias após a emergência (DAE). Aos 14 DAE, as cultivares Carajás, IAC 202, BRS Sertaneja, BRS Bonança e BRS Curinga apresentaram elevada atividade desta enzima. Aos 21 DAE, a atividade da NR foi superior nas cultivares Primavera e BRS Bonança. Entretanto, aos 28 DAE, não houve diferenças entre as cultivares quanto a esta variável. Conclui-se que atividade da enzima NR, na cultura do arroz de terras altas, é dependente da cultivar, do período de desenvolvimento vegetal e decresce com o avanço do ciclo da cultura.
Nitrate reductase enzyme activity in upland rice cultivars
Keywords: Ammonium; Nitrogen; Oryza sativa; No-tillage system; Amônio; Nitrogênio; Oryza sativa; Sistema de plantio direto